Proceedings of the 13th International Conference on World Wide Web 2004
DOI: 10.1145/988672.988710
|View full text |Cite
|
Sign up to set email alerts
|

A method for transparent admission control and request scheduling in e-commerce web sites

Abstract: This paper presents a method for admission control and request scheduling for multiply-tiered e-commerce Web sites, achieving both stable behavior during overload and improved response times. Our method externally observes execution costs of requests online, distinguishing different request types, and performs overload protection and preferential scheduling using relatively simple measurements and a straightforward control mechanism. Unlike previous proposals, which require extensive changes to the server or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
168
0
8

Year Published

2008
2008
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(179 citation statements)
references
References 30 publications
3
168
0
8
Order By: Relevance
“…Several studies investigated the effects of request scheduling and prioritization on web server performance, for general database-driven dynamic web sites (Elnikety et al, 2004), and for eCommerce web sites in particular (Schroeder et al, 2006;Alonso et al, 2007;Zhou et al, 2006). It was shown that request response times and server throughput can be improved by employing such scheduling algorithms as Shortest Job First (SJF) (Elnikety et al, 2004) and Shortest Remaining Processing Time First (Verma and Ghosal, 2003).…”
Section: Related Work and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies investigated the effects of request scheduling and prioritization on web server performance, for general database-driven dynamic web sites (Elnikety et al, 2004), and for eCommerce web sites in particular (Schroeder et al, 2006;Alonso et al, 2007;Zhou et al, 2006). It was shown that request response times and server throughput can be improved by employing such scheduling algorithms as Shortest Job First (SJF) (Elnikety et al, 2004) and Shortest Remaining Processing Time First (Verma and Ghosal, 2003).…”
Section: Related Work and Discussionmentioning
confidence: 99%
“…It was shown that request response times and server throughput can be improved by employing such scheduling algorithms as Shortest Job First (SJF) (Elnikety et al, 2004) and Shortest Remaining Processing Time First (Verma and Ghosal, 2003). Some of these studies used request scheduling algorithms combined with admission control policies (Chen et al, 2001;Elnikety et al, 2004).…”
Section: Related Work and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Admission control is already widely used in telecommunications. Research has also been performed on the use of admission control for Web Servers; see for instance [1]- [3], [7]. The use of WAC to prevent overload for stand alone Web Services has been discussed in [4]- [5].…”
Section: Introductionmentioning
confidence: 99%